Global Supply Chain Disruption During COVID 19 (International Journal of Innovative Research in Engineering & Management, 2023)
The COVID-19 epidemic has seriously  harmed a number of sectors worldwide. A variety of raw  materials, intermediate products, and finished goods  availability and supply were given considerable  consideration. Becoming irritated. The global supply  chain (GSC), which over the years has shown itself to be  very powerful and durable in the face of various shocks,  is actually compromised. This paper uses critical reading,  event causal analysis, and data to examine how COVID 19 has affected the effectiveness and responsiveness of  CSS and makes a number of management  recommendations to reduce risk and foster resilience  across a range of industrial sectors. the branch. According  to research, the COVID-19 pandemic has caused the  majority of CSS, including the pharmaceutical, food,  agricultural, electronics, and automotive industries, to  operate with hitherto unheard-of disruption. Contrary to  prior severe interruptions, COVID-19 has negatively  impacted GSC's operations at every level, causing  considerable fluctuations in demand as well as significant  volatility in the processes of manufacturing, processing,  transportation, and logistics. According to the report,  strengthening supply chain resilience is crucial for  lowering vulnerability during disruptions. Additionally,  the data demonstrates that the post-COVID-19 CSS will  often be shorter as a result of enhanced tactics that place a  greater emphasis on resettlement and back-shoring.
Keywords: Supply Chain; Pandemic; Disruption of Supply Chain; Supply networks